Infiltrative Lung Diseases: Complications of Novel Antineoplastic Agents in Patients with Hematological Malignancies - Bobbak Vahid; Paul E Marik (Canadian Respiratory Journal)
Infiltrative lung disease is a well-known complication of antineoplastic agents in patients with hematological malignancies. Novel agents are constantly being added to available treatments. The present review discusses different pulmonary syndromes, pathogenesis and management of these novel agents.